Effect of Surcharges to The Stability of Mechanically Stabilized Earth Wall Using Finite Element Method: Back Analysis Study Case in Senai City Airport - Md. Dan@Azlan, Mohd Firdaus; Alias, Muhammad Amirul Nurhakim (Journal of Sustainable Underground Exploration, 2022)
Abstract: Mechanically Stabilized Earth (MSE) wall is a composite retaining structure construction made up of alternating layers of compacted backfill and soil reinforcing components. Surcharges on top of MSE wall is one of the factors that can lead to the failure of the MSE wall. In Senai City Airport, a MSE wall with high 9 m and length up to 400 m has been constructed. However, the effect of various surcharges of the MSE wall slope did not well investigate and was poorly understood. This study aims to investigate the effect of surcharge to the stress behaviour and the factor of safety of Mechanically Stabilized Earth Wall (MSE) wall using Finite Element Method (FEM). The study conducted using different loads in order to determine the stress behaviour and the safety factor of MSE wall using PLAXIS software. The geometry and parameters of sandy silt slope of Senai City Airport, Senai, Johor was taken from design consultant and previous soil investigation report, respectively. The soil parameters were used in this study are the unit weight of the soil, cohesion, Poisson Ratio, Young Modulus and the friction angle. This study gave the best result in order to determine the effect of surcharges to the behaviour of stress and safety factor of MSE wall. The highest total displacement was at 100 kN with total displacement 19.23m with 0.884 factor of safety. This study revealed the effect of various surcharges on the behaviour of stress and factor of safety of the MSE wall. The increase of surcharge increased the stress behind the wall and increased the factor of safety (FOS) when the loads was increased.